2008
DOI: 10.1103/physrevb.78.054105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mo on the Fe:Mo:C nanocatalyst thermodynamics for single-walled carbon nanotube growth

Abstract: We explore the role of Mo in Fe:Mo nanocatalyst thermodynamics for low-temperature chemical vapor deposition growth of single walled carbon nanotubes (SWCNTs). By using the size-pressure approximation and ab initio modeling, we prove that for both Fe-rich (∼ 80% Fe or more) and Mo-rich (∼ 50% Mo or more) Fe:Mo clusters, the presence of carbon in the cluster causes nucleation of Mo2C. This enhances the activity of the particle since it releases Fe, which is initially bound in a stable Fe:Mo phase, so that it ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 62 publications
2
31
2
Order By: Relevance
“…8 Thermodynamic calculations suggested that Mo 2 C enhances the activity of Fe-Mo NPCs by releasing free iron atoms while the formation of Fe carbides such as Fe 3 C and (Fe,Mo) 23 C 6 interferes with the growth of single-walled CNTs (SWNTs). 33 Contrary to these arguments, our ETEM study on Mo-added Fe-catalyzed CVD has shown that molybdenum leads to (Fe,Mo) 23 C 6 -type carbide NPCs and that Mo 2 C is not observed in our CVD condition. On the other hand, several authors suggested that molybdenum inhibits the diffusion of metal species such as Co on substrates, keeping the size of NPCs suitable for the growth of SWNTs.…”
contrasting
confidence: 69%
“…8 Thermodynamic calculations suggested that Mo 2 C enhances the activity of Fe-Mo NPCs by releasing free iron atoms while the formation of Fe carbides such as Fe 3 C and (Fe,Mo) 23 C 6 interferes with the growth of single-walled CNTs (SWNTs). 33 Contrary to these arguments, our ETEM study on Mo-added Fe-catalyzed CVD has shown that molybdenum leads to (Fe,Mo) 23 C 6 -type carbide NPCs and that Mo 2 C is not observed in our CVD condition. On the other hand, several authors suggested that molybdenum inhibits the diffusion of metal species such as Co on substrates, keeping the size of NPCs suitable for the growth of SWNTs.…”
contrasting
confidence: 69%
“…Size-induced stabilization present at the nanoscale 44,45 may promote stability at higher temperature for nanodispersed precipitates. Although the mechanical properties would not modify the solidsolution Mg-Li appreciably, the overall effect in thermal and electric transport can be dramatic, as it has been shown for nanoprecipitates in semiconducting materials.…”
Section: Discussionmentioning
confidence: 99%
“…Surface segregation may also change at small particle sizes ͑less than ϳ2 nm in diameter͒ as the surface energy changes 42 and surfacetension effects might become relevant. 43,44 These approximations could affect the equilibrium stability 45,46 if the magnitude of the segregation energies were not as strong as the ones we found ͑e.g., the smallest ͉ Fe ͑1͒ Cu ͉ / k B Ӎ 4677 K͒.…”
mentioning
confidence: 89%